"Women easily feel that they have lost a year if they don`t ski faster": Finnish ski coaches` discursive constructions of gendered dual career pathways - Saarinen, M.; Ryba, T. V.; Kavoura, A.; Aunola, K. (Psychology of Sport and Exercise, 2023)
Objectives Earlier qualitative researchers studying athletes` dual careers (DCs) have shown that sociocultural discourses on gender are ingrained in DC policies and practices, creating gender inequalities and hierarchies. In this study, we aimed to extend this body of research by examining how Finnish elite youth ski coaches discursively construct athletes` education and gender in their talk and coaching practices. Similarly, we examined how coaches` beliefs about athletes' holistic development are interlinked with broader sociocultural discourses on gender.